Pengaruh Video Animasi Terhadap Perkembangan Kognitif Dalam Mengenalkan Binatang Ternak Pada Anak Usia Dini Di Taman Kanak-Kanak Sabbihisma 2 Padang - Meiza, Bahta Meiza Nurfitri; Rakimahwati, Rakimahwati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
The purpose of this study is to discuss the results of research on the effect of animated videos on children's cognitive development in introducing farm animals to early childhood at Sabbihisma 2 Padang Kindergarten. In the introduction of farm animals, children have not used video animation media and still use simple media such as picture cards so that children get bored easily. Researchers conducted this research to help children get to know farm animals by using animated video media. This study used a Quasi-Experimental Method with a design with a total population of 66 children in Sabbihisma 2 Padang Kindergarten, the sample of this study consisted of B6 class, namely the control class and B3 control class, where there were 10 children in B6 class and 10 B3 class. children, with a total of 20 children. Data collection techniques used tests in the form of statements totaling 5 items and data analysis techniques using normality tests, homogeneity tests, hypothesis testing with the help of SPSS 20 computerization. -test of 0.127 and after treatment was 0.00 and stated <0.05. Thus it can be concluded that there is a significant effect on cognitive development in introducing farm animals to early childhood at Sabbihisma 2 Padang Kindergarten.